Studi Literatur: Penerapan Model Discovery Learning terhadap Hasil Belajar Peserta Didik pada Materi Klasifikasi Makhluk Hidup - Mas Akhbar Faturrahman; Kurnia Ningsih (Departement of Mathematics Education, 2023)
Learning is the main component in the educational process, so a learning design is needed to support an increase in students' understanding of concepts. Learning outcomes as a product of conceptual understanding must show a good level after the learning process occurs. One biology material that tends to be difficult for teachers and students is the classification of living things. The discovery learning model is the solution to improve student learning outcomes in this material. This study aimed to conduct a study of various studies related to implementing the discovery learning model to improve student learning outcomes in the classification of living things. This research used the literature study method on various scientific articles from national journals and proceedings in the last ten years. From the search results, 19 scientific articles were obtained, which were analyzed to prove that the discovery learning model can improve student learning outcomes in the classification of living things.